2020
DOI: 10.1177/0004944120982756
|View full text |Cite
|
Sign up to set email alerts
|

The role of teachers in mitigating student stress to progress learning

Abstract: Many Australian young people experience mental health concerns, academic and study-related stresses, and socio-economic pressures. Phenomenological research conducted among primary and secondary schoolteachers in four Australian states investigated how teachers manage student wellbeing concerns and academic pressures and stresses. Findings identify key stresses that affect students’ performance and how teachers respond to these stresses to progress student learning. Creating space, finding margin, mitigating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…A student suffering from anxiety may find it challenging to participate actively in the class. The teacher plays a crucial role in identifying symptoms of different mental and physical disorders like anxiety, irritability, mood disorder, and eating disorders in students and finding solutions to resolve these (Willis et al 2020 ). A teacher is that important person who can contribute as a counselor, tutor, and parent by adopting several strategies to cope with students’ problems according to their needs, as teachers spend a large amount of time in contact with their students (Willis et al 2019 ).…”
Section: The Role Of Teachers In Students’ Mental Well-beingmentioning
confidence: 99%
“…A student suffering from anxiety may find it challenging to participate actively in the class. The teacher plays a crucial role in identifying symptoms of different mental and physical disorders like anxiety, irritability, mood disorder, and eating disorders in students and finding solutions to resolve these (Willis et al 2020 ). A teacher is that important person who can contribute as a counselor, tutor, and parent by adopting several strategies to cope with students’ problems according to their needs, as teachers spend a large amount of time in contact with their students (Willis et al 2019 ).…”
Section: The Role Of Teachers In Students’ Mental Well-beingmentioning
confidence: 99%
“…Relying on transactional theories of stress (e.g., Lazarus, 1966;Lazarus and Folkman, 1984) we assume that reducing instructors' stress by reducing their cognitive overload will, by extension, benefit the students. Previous research has demonstrated that instructors play a key role in mitigating students' stress to progress learning (Willis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the academic pressure experienced by students will have a negative influence on many factors. Previous studies have shown that academic pressure can have an impact on students' psychology (Lee et al, 2021;Lu, Nie and Sousa-Poza, 2021;Willis et al, 2021;Jiang et al, 2022;McLean, Gaul and Penco, 2022;Ramgoolam-Atchiamith et al, 2022;Wu, Ma and Luo, 2022;Brown et al, 2023). The results of previous research indicate that when students experience academic pressure, individual energy will be used up enormously, which can result in a decrease in their learning efficiency, they are depressed, low psychological well-being, low mental health, anxiety, fear, and other adverse psychological reactions.…”
Section: Consequence Of Academic Pressure On Student 1 Psychological ...mentioning
confidence: 99%